Sosialisasi Penggunaan Aplikasi Sistem Informasi Gender dan Anak Tingkat Kota Kendari Tahun 2023 - Darman, Darman; Arbiansyah, Arbiansyah; Saputra, Faldi; Aksa, Ikhuzain Maftuh (FAKULTAS TEKNIK UMKENDARI, 2023)
The lack of availability of gender and child data in the city of Kendari has resulted in unresponsive policies or programs implemented by the government. Gender data on children's funds is really needed as input for development planning in all fields, including the development of women's empowerment and child protection. In Kendari City, gender and child data has not been recorded in a systematic database, making it difficult for policy makers, so a system is needed that makes it easier to manage and analyze this data. Thus, the Kendari City Women's Empowerment and Child Protection Service introduced the relevant agencies and agencies to the Gender and Children Information System Application. This activity was carried out in the form of socialization, which was attended by 51 participants from various agencies and sub-districts in Kendari city. With the success of this activity, it is hoped that the commitment and responsibility of data managers at the Kendari City Women's Empowerment and Child Protection Department will be able to provide and present gender and child data and analysis as well as contribute actively to the implementation of the Kendari City Gender and Child Information System Application.